RIGHT PARA DUODENAL HERNIA: A CASE REPORT - Deherkar, Juthikaa; Borkar, Pravin; Bansode, Pankaj; Inamdar, Swati; Sindhe, Sudhir; Raiyani, Tejas; Doshi, Anirudha (International Journal of Clinical and Biomedical Research, 2018)
Paraduodenal hernia (PDH), a rare congenital anomaly, is a type of internal hernia which occurs due to a defect in the reduction and rotation of the midgut. On anatomical and embryological basis, PDH can be broadly divided into right- and Left PDH. Right PDH is rarer than its counterpart. We present a case of Right PDH. The patient presented with a history of pain in abdomen since last 1 year with intermittent episodes of vomiting. Patient was admitted in various institutions previously but was managed conservatively. On investigation patient was diagnosed to have right side paraduodenal hernia on CT abdomen. The jejunal loops had herniated through the fossa of Waldeyer. Jejunal loops reduced from the hernia sac and sac excised, fibrotic edges incised and defect widened. Post operatively recovery was uneventful. The rarity of this condition and the need for early diagnosis, to prevent the high risk of bowel obstruction and strangulation, makes PDH one of the difficult challenges for the clinicians.